America's Paul Revere - Forbes, Esther (Houghton Mifflin Company Boston, 1946)
A biography of the patriot of the Revolution who had many trades, among them silver work, manufacture of copper, casting of bells, engraving, and dentistry.
1000L
Keywords: Revere, Paul -- 1735-1818; Statesmen -- Massachusetts -- Biography -- Juvenile literature; United States -- History, Revolution, 1775-1783 -- Biography -- Juvenile literature